Fever in a Patient with a Central Venous Catheter Colonized by Pandoraea pnomenusa - Susana Ramos Oliveira; Isabel Costa Monteiro; Cristina Rodrigues; Maria João Soares (Acta Médica Portuguesa, 2022)
Pandoraea species are a newly described genus of multidrug-resistant, non-fermentative Gram-negative bacilli, mainly isolated from sputum samples of cystic fibrosis patients. In immunocompromised patients or with high antibiotic selective pressure, these pathogens are generally opportunistic and invasive. Although Pandoraea spp. are rare, the true incidence of these infections may be underestimated due to difficulties in microbial identification by phenotypic methods. We present the case of a 51-year-old woman, with new-onset fever after a prolonged hospitalization and multiple courses of antibiotics. Mass spectrometry assays identified Pandoraea pnomenusa in the blood cultures taken from the central venous catheter and in the catheter tip. Fever cessation after catheter removal suggests a catheter-related bloodstream infection. To the best of our knowledge, this is the first isolation of a Pandoraea spp. in Portugal, which should raise awareness to the emergence of these opportunistic and multidrug-resistant microorganisms, and the importance of its prompt identification.